Smart Grid - BEMS: The Art of Optimizing the Connection between Comfort Demand and Energy Supply - Aduda, Kennedy; Zeiler, Wim; Boxem, Gert (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
Comfort demands are increasing while at the same there is a need for energy reduction and the use of renewable energy sources within Smart Grids. Functionality of Buildings Energy Management Systems (BEMS) need re-evaluation in the context of smart grid environment. In particular, their inability for real time feedback and a rather static mode of operations requires attention in the light of smart grid operations. By using a multi agent system in combination with traditional BEMS, a layered process control system at building level that conceptualises energy demand interactively with the smart grid supply infrastructure and the environment is possible. Practical contribution is improved energy management by balancing energy demand and energy supply. The paper discusses optimisation of BEMS operations for energy efficiency and indoor human comfort using multi-agents system (MAS) technology in the Smart Grid environment. A conceptual framework for improving the effectiveness BEMS in the realm of smart grids operation and distributed generation using MAS is presented .